Social policy and crash fatalities: a multivariate time series analysis - Chamlin, Mitchell B. (Journal of crime and justice, 2018)
This paper is concerned with changes over time in road safety. Most research, rooted in the deterrence hypothesis, focuses on the impact of reductions in the blood alcohol concentration (BAC) limits on crash-related fatalities. Our study, drawing on opportunity theories of social action, extends this research by examining the relative effects of safety innovations, exposure risk, and changes in BAC limits, on deaths resulting from motor vehicle accidents. The multivariate time series analyses indicate that the implementation of seatbelt legislation and the number of vehicle miles traveled directly affect, while the reduction of BAC limits indirectly affects, the number of crash-related fatalities. The implication of these findings for determining the optimal research design for assessing the impact of legislative initiatives on crash-related injuries and deaths are discussed.